PELATIHAN PERENCANAAN KEUANGAN : KESEHATAN KEUANGAN KELUARGA - Heriyanto, Heriyanto; Sri Mendari, Anastasia; Suci Kewal, Suramaya; Andri Putranto, Yohanes; Widyartono, Agustinus; Yevira, Yevira (Universitas katolik Musi Charitas, 2023)
The activities of the Marriage Preparation Course are under the coordination of the 1st Deanof Palembang Archdiocese. Family Commission Dean 1 Palembang Archdiocese is a partnerin community service activities with a family financial planning training program. The numberof participants in this activity was 35 people, 52% male and 48% female, mostly aged 23-27years (49%), and most of them had incomes ranging from IDR 2,000,000 – IDR 4,000,000(35%). Participants are young couples who plan to have a Catholic wedding. This activity hasthe theme of Financial Planning Training: Family Financial Health. The purpose of thisactivity is so that KPP participants have the skills to prepare balance sheets and cash flowreports for family finances. Through financial management skills, participants are expected tobe able to realize family financial health. During the activity, participants were asked to identifysources of funds and allocation of funds that have been carried out so far and carry outfinancial health checks based on patterns of financial management. The training processcovers several stages namely Awareness, Knowledge, and Simulation Activities. Through thisactivity, participants gain insight into good family financial planning. Participants also knowthe level of health related to the current condition of family financial management.